2006
DOI: 10.1161/01.res.0000197785.51819.e8
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules Modulate the Stiffness of Cardiomyocytes Against Shear Stress

Abstract: Abstract-Although microtubules are involved in various pathological conditions of the heart including hypertrophy and congestive heart failure, the mechanical role of microtubules in cardiomyocytes under such conditions is not well understood. In the present study, we measured multiple aspects of the mechanical properties of single cardiomyocytes, including tensile stiffness, transverse (indentation) stiffness, and shear stiffness in both transverse and longitudinal planes using carbon fiber-based systems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 43 publications
8
64
0
Order By: Relevance
“…We showed that the transverse stiffness in cardiomyocytes from hearts with ISO-induced hypertrophy was reduced by cross-bridge inhibition (actin-myosin interaction) using BDM and blebbistatin. Thus, the present results indicate that longitudinal shear stiffness is increased by polymerization of microtubules 42 and that transverse (indentation) stiffness is also increased by residual cross-bridge formation under pathological conditions. It remains unclear which direction of stiffness contributes to deterioration of diastolic function.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…We showed that the transverse stiffness in cardiomyocytes from hearts with ISO-induced hypertrophy was reduced by cross-bridge inhibition (actin-myosin interaction) using BDM and blebbistatin. Thus, the present results indicate that longitudinal shear stiffness is increased by polymerization of microtubules 42 and that transverse (indentation) stiffness is also increased by residual cross-bridge formation under pathological conditions. It remains unclear which direction of stiffness contributes to deterioration of diastolic function.…”
supporting
confidence: 57%
“…Nishimura et al succeeded in measuring multiple aspects of the mechanical properties of single cardiomyocytes from normal rat hearts, including tensile stiffness, transverse (indentation) stiffness, and shear stiffness in both the transverse and longitudinal planes. 42 Of all the measurements, only the stiffness against shear in the longitudinal plane of normal cardiomyocytes was modulated by the microtubule cytoskeleton. For pathological conditions, they measured longitudinal shear stiffness in myocytes from a hamster model of cardiomyopathy.…”
mentioning
confidence: 99%
“…In contrast, in AVCMs and skeletal muscle fibers, mitochondria are spatially confined to the space among the myofilaments and have no opportunity to move toward distant mitochondria. This might account for the lower frequency of fusion events seen in cultured AVCMs and other differentiated muscle paradigms (17,45). In addition to the structural confinement of mitochondria, in vivo and cell culture conditions seem to affect mitochondrial motility differently, with mitochondria showing little movement in freshly isolated striated and vascular smooth muscle but vigorous displacement in proliferating cultured striated and smooth muscle cells (17,46).…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyocytes microtubules play a role in resisting shear stress (Nishimura et al, 2006) and are important in modulating the progression of cardiac hypertrophy (Cooper, 2006). Thus it is tempting to speculate that INF1 may also play a role in these processes.…”
Section: Discussionmentioning
confidence: 99%